The effects of bank mergers : case study on DBS Bank-POSBANK merger - Kwok, Sherlayne Chong Yen (2008)
This paper looks at one of them -- the DBS Bank - POSBank merger and evaluates the effects of the merger on the general performance of the merged bank vis-à-vis three other local banks. The research findings provided support for all (except for one) of the hypotheses proposed, namely the merger would lead to increases in profitability, efficiency in managing expenses, market power, share price; and the merged bank would adopt a more aggressive approach towards investments.